Triazine-COF@Silicon nanowire mimicking plant leaf to enhance photoelectrocatalytic CO2 reduction to C2+ chemicals - Wenrui Wan; Fanhua Meng; Si Chen; Jianhua Wang; Chunyan Liu; Yan Wei; Chenpu He; Li Fan; Qiaolan Zhang; Weichun Ye; Huanwang Jing (Green Energy & Environment)
Converting CO2 and water into valuable chemicals like plant do is considered a promising approach to address both environmental and energy issues. Taking inspiration from the structures of natural leaves, we designed and synthesized a novel copper-coordinated covalent triazine framework (CuCTF) supported by silicon nanowire arrays on wafer chip. This marks the first-ever application of such a hybrid material in the photoelectrocatalytic reduction of CO2 under mild conditions. The Si@CuCTF6 heterojunction has exhibited exceptional selectivity of 95.6% towards multicarbon products (C2+) and apparent quantum efficiency (AQE) of 0.89% for carbon-based products. The active sites of the catalysts are derived from the nitrogen atoms of unique triazine ring structure in the ordered porous framework and the abundant Cu–N coordination sites with bipyridine units. Furthermore, through DFT calculations and operando FTIR spectra analysis, we proposed a comprehensive mechanism for the photoelectrocatalytic CO2 reduction, confirming the existence of key intermediate species such as ∗CO2−, ∗=C=O, ∗CHO and ∗CO–CHO etc. This work not only provides a new way to mimic photosynthesis of plant leaves but also gives a new opportunity to enter this research field in the future.